THE RHETORIC OF DA’WAH IN THE TIKTOK ERA: AN ANALYSIS OF DIGITAL PREACHERS’ COMMUNICATION STYLES AND THEIR INFLUENCE ON GENERATION Z IN INDONESIA - Rahman, Khalid; Anis, Nina; Vann, Dara; Pong, Ming (Journal International Dakwah and Communication, 2025)
The proliferation of short-form video content on platforms like TikTok has created a new frontier for Islamic preaching (da’wah), fundamentally altering how religious messages are communicated to younger audiences. This digital shift poses new challenges and opportunities, particularly in engaging Generation Z in Indonesia, a demographic highly active on the platform. This research aims to analyze the rhetorical communication styles of prominent Indonesian digital preachers on TikTok and to assess their influence on the religious perceptions and engagement of Generation Z. Employing a qualitative methodology combining virtual ethnography and critical discourse analysis of popular da’wah videos, complemented by online interviews with Gen Z users, this study delves into contemporary Islamic communication. The results identify a predominant use of relatable storytelling, humor, and trend-integration as key rhetorical strategies. These styles foster high engagement and a personalized religious connection among youth but also risk oversimplifying complex theological issues. In conclusion, the rhetoric of da’wah on TikTok marks a significant evolution in religious discourse, effectively capturing the attention of Generation Z but also highlighting a critical need for digital religious literacy to ensure deeper understanding.